Responsible Hospitality: Inclusive, Active, Green - Gorenak, Mitja; Trdina, Andreja (2018)
The book broadens the reach of Tourism studies by providing comprehensive and rigorous examinations of many issues related to Responsible Tourism development. The collection considers the subject of Responsible Hospitality broadly, and in line with concerns for the social, cultural, economic and natural environment. It provides a distinctive and balanced overview of both theoretical issues and practical cases. Starting from the perspective that commitments to accessibility and social inclusiveness are the ultimate frame of reference for Responsible Tourism development, in part 1) the collection first provides contributions on Accessible Tourism and social sustainability through the principle of inclusion. In the context of the rising demand for all-encompassing and in-depth experiences, the contributions presented in Part 2) contribute to understanding of Active Tourism and Sports Tourism. Finally, the authors of contributions also examine the issues of Responsible Tourism development in the context of green, healthy and local from three different perspectives: That of tourists, local (service) providers, and from the governance level. The overall aim of the book is, thus, to construct a vision of hospitality that operates in a manner that supports people and communities, promotes responsible environmental consumption, and is socially inclusive.
Keywords: hospitality; responsibility; Accessible Tourism; Active Tourism; Sport Tourism; green; local